Factors that interfere in the delivery and birth process: an integrative literature review (Research, Society and Development, 2020)
For considering childbirth and birth as a unique process with specificities that interfere in the lives of the people involved, especially for the mother, child and family; We sought to identify scientific evidence in the national and international literature the factors that interfere in the process of childbirth and birth. This is an integrative literature review carried out in the databases of Latin American and Caribbean Literature in Health Sciences (LILACS) and Publisher Medline (PubMed), with the descriptors "childbirth" and "pregnant women". 734 studies were found, of which 41 were included in the study. In prenatal care, health education actions are an essential element for preparing for childbirth. It was highlighted that the use of innovative methodologies must be combined with personal contact, bonding and the valuation of singularities and integrality. Still, it became evident that the birth process is considered a ritual of passage and that this experience gives new meaning and gives meaning to the life of the woman and her family. Therefore, the support received by midwives was identified as a differential. However, obstetric care is shown to be fragmented, the binomial mother and child do not have their well-being prioritized. Parturients still wander through the maternity hospitals in search of care, where they are attended with inadequate interventions and abuse of professional and institutional power. It is necessary to change the paradigm, through professional qualification, of training that sensitize humanized, integral and safe care, supported by scientificity and by rescuing the valorization of childbirth and birth as a physiological and social event.